2018
DOI: 10.1002/brb3.987
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital identification of factors associated with death during one‐year follow‐up after acute stroke

Abstract: ObjectivesIn acute stroke, the risk of death and neurological sequelae are obvious threats. The aim of the study was to evaluate the association between various clinical factors identified by the emergency medical service (EMS) system before arriving at hospital and the risk of death during the subsequent year among patients with a confirmed stroke.Material and MethodsAll patients with a diagnosis of stroke as the primary diagnosis admitted to a hospital in western Sweden (1.6 million inhabitants) during a fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…Death has always been a major threat to acute cerebral infarction. Several studies have found that the severity of admission symptoms, insular infarction, and cerebral infarction in patients with acute cerebral infarction are independent predictors of clinical prognosis [ 27 , 28 ]. We followed up the patients in the observation group for one year and found that the one-year survival rate was 71.05%.…”
Section: Discussionmentioning
confidence: 99%
“…Death has always been a major threat to acute cerebral infarction. Several studies have found that the severity of admission symptoms, insular infarction, and cerebral infarction in patients with acute cerebral infarction are independent predictors of clinical prognosis [ 27 , 28 ]. We followed up the patients in the observation group for one year and found that the one-year survival rate was 71.05%.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a serious condition most often caused by a respiratory or a cardiac dysfunction, and a neurological assessment may be more difficult to perform in a hypoxic patient. It has also been shown that hypoxic stroke patients have a considerably higher mortality rate than non‐hypoxic stroke patients . It is of great importance not only to diagnose stroke correctly but also to diagnose and treat cardiopulmonary comorbidity correctly.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the prehospital stroke care in western Sweden in a large observational study . The aim of this sub‐study was to investigate those patients in whom a suspicion of stroke was raised by the EMS clinician before hospital admission and to compare clinical characteristics, circumstances at symptom onset, and clinical symptoms among patients with a final diagnosis of stroke or TIA with patients with other final diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The risk increased even above 90%. Previous studies have indicated that low oxygen saturation in the early phase is associated with an increased risk of adverse events amongst patients with acute myocardial infarction [ 25 ] and an increased risk of death amongst patients suffering from stroke [ 26 ]. The mechanisms behind these findings can only be speculated upon.…”
Section: Discussionmentioning
confidence: 99%